Parental Engagement in Children's Online Learning During COVID-19 Pandemic - Ria Novianti; Meyke Garzia (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2020)
The world is shaken as the Covid-19 pandemic. All aspects of human life feel the consequences, including the education. School activity is replaced by online learning at home and teachers is now sharing the burden of teaching with parents. Facing this situation, parents should be able to play a role as children's learning companions at home. In fact, not all parents are ready for this new task. This research aims to find out more about the parental engagement in children's online learning during the Covid-19 pandemic. Research conducted in Riau province with 148 samples of parents from the first and second grade of elementary school students, who filled the online questionnaire. The design used in this study is a converging design, simultaneously collecting quantitative and qualitative data, combining the data, comparing the results, and explaining all descriptions in the results. The result shows that parental engagement in supervising the children study time is 81,7%, parent role in accompanying children in learning is 80,4%, supervising children study time is 71,8%, recognizing children learning difficulties 69% and providing learning facilities 64.8%. It can be concluded that most of the parents are engaged in children online learning activities, although there are still those who have obstacles and difficulties in dividing time, attention and explaining the lesson to childrens.